2020
DOI: 10.3390/jmmp4010022
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanism of Damage of the Graphite Spheroid in the Nodular Cast Iron During Static Tensile Test

Abstract: This work was focused on two particular phenomena contributing to a damage process of nodular cast iron under tensile stress: Internal destruction of graphite nodule and debonding at graphite/matrix (G-M) interface. The G-M debonding was analyzed depending on the phase characteristics of the metal matrix and with the increase in the distance of the observation field from the main crack surface. Typical morphological effects of decohesion in the graphite-matrix microregions related to an internal structure of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…This type of destruction is correlated to the complex wear in the presence of heat when the metastable secondary structure of the second order (formed ceramic plaques with the width of 25-30 μm for the sample machined in water and non-homogenous plaques of 8-10 μm in oil) is adherent to the heat-affected surface of the base nanocomposte. The formed surface and subsurface layers under this type of wear have the presence of partial removal of the secondary structures, which are more brittle in the case of machining in water ( Figure 14) [78,79,[84][85][86][87][88]. In the context, zinc oxide (ZnO) formed during machining in oil is an n-type semiconductor and sublimates at a temperature of 1800 °C [89,90]; copper (II) oxide (CuO) that is observed after machining in water does not react with an aqueous medium and decomposes to metallic copper in the presence of hydrogen, carbon, or carbon monoxide [91,92]:…”
Section: Discussionmentioning
confidence: 99%
“…This type of destruction is correlated to the complex wear in the presence of heat when the metastable secondary structure of the second order (formed ceramic plaques with the width of 25-30 μm for the sample machined in water and non-homogenous plaques of 8-10 μm in oil) is adherent to the heat-affected surface of the base nanocomposte. The formed surface and subsurface layers under this type of wear have the presence of partial removal of the secondary structures, which are more brittle in the case of machining in water ( Figure 14) [78,79,[84][85][86][87][88]. In the context, zinc oxide (ZnO) formed during machining in oil is an n-type semiconductor and sublimates at a temperature of 1800 °C [89,90]; copper (II) oxide (CuO) that is observed after machining in water does not react with an aqueous medium and decomposes to metallic copper in the presence of hydrogen, carbon, or carbon monoxide [91,92]:…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent update of the slip rates of each slip system ensures the accumulation of plastic strain in already damaged elements with ongoing deformation, whereby damage can propagate, if the resolved shear stress again exceeds the CRSS. It was assumed that relevant damage occurs only in the ferrite phase which is considered to be justified since the debonding between the graphite nodules and the ferrite phase starts at an early stage of deformation and the damage leading to a macroscopic failure of the DCI structure is characterized by large accumulation of plastic deformation in the ferritic matrix [ 44 , 48 , 49 ]. The interface between graphite nodules and ferrite matrix is modeled as ideal, i.e., possible debonding is not considered in the models in this work.…”
Section: Methodsmentioning
confidence: 99%
“…In situ investigations on ADI plastic and fracture behavior have been reported [65][66][67], even if the main focus of these investigations was on the effects of graphite nodule cracking and graphite-matrix debonding on fracture evolution, rather than on ausferrite plastic behavior. Furthermore, these in situ investigations were only on flat small-sized tensile specimens not complying with international standards.…”
Section: Tensile Behavior Of 25 MM Y-blocks With Round Tensile Specim...mentioning
confidence: 99%
“…Furthermore, these in situ investigations were only on flat small-sized tensile specimens not complying with international standards. In [67], it was reported that austenite caused some delays in the graphite-matrix debonding, while with bainitic ferrite, the debonding was easier and cracks propagated alongside the ferrite-austenite boundaries [65]. It could be speculated that these observations concerned the external surfaces of flat tensile specimens, causing ductility reduction, while in round tensile specimens, these mechanisms might be less active because of the reduction of the surface/volume ratio of the strain gauge.…”
Section: Tensile Behavior Of 25 MM Y-blocks With Round Tensile Specim...mentioning
confidence: 99%